2017
DOI: 10.5812/jjhs.64051
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Design of Illumination in a Steel Manufacturing Company in Ahvaz, Iran

Abstract: Background: Illumination is a physical factor in workspaces. This factor is an important risk factor for vision health, employees comfort, preventing accidents etc. and should be standardized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…de Kort and Smolders observed that the extent of lighting affects the psychological and biological processes, where those exposed to sufficient light showed greater awareness and energy than those exposed to poor lighting (5). The illumination provided inside buildings improves the limited sunlight in them, enabling individuals to be active at different times of the day (6). Learning occurs with 83% eyesight, where impaired vision causes reduced educational efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…de Kort and Smolders observed that the extent of lighting affects the psychological and biological processes, where those exposed to sufficient light showed greater awareness and energy than those exposed to poor lighting (5). The illumination provided inside buildings improves the limited sunlight in them, enabling individuals to be active at different times of the day (6). Learning occurs with 83% eyesight, where impaired vision causes reduced educational efficiency.…”
Section: Introductionmentioning
confidence: 99%